L-correspondences: the inclusion Lp(μ,X)⊂Lq(ν,Y) - C. Bryan Dawson (International Journal of Mathematics and Mathematical Sciences)
In order to study inclusions of the type Lp(μ,X)⊂Lq(ν,Y), we introduce the notion of an L-correspondence. After proving some basic theorems, we give characterizations of some types of L-correspondences and offer a conjecture that is similar to an equimeasurability theorem.